2021
DOI: 10.1371/journal.pone.0249865
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of stillbirth among women who had given birth in Southern Ethiopia, 2020: A case-control study

Abstract: Background Although the rate of stillbirth has decreased globally, it remains unacceptably high in low- and middle-income countries. Only ten countries including Ethiopia attribute more than 65% of global burden of still birth. Ethiopia has the 7th highest still birth rate in the world. Identifying the predictors of stillbirth is critical for developing successful interventions and monitoring public health programs. Although certain studies have assessed the predictors of stillbirth, they failed in identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
(53 reference statements)
4
15
0
Order By: Relevance
“…Moreover, results from different studies revealed maternal age above 35, place of residence, level of education, parity, antenatal care (ANC) utilization, place of delivery and mode of delivery, maternal infection and a variety of maternal medical conditions, feto-maternal complications related to pregnancy and labor, inadequate care during pregnancy and immediate childbirth, obstructed/prolonged labor, antepartum hemorrhage, preterm labor, premature rupture of membrane, and intrauterine growth restriction are common obstetric determinants associated with an increased risk of stillbirths, and particularly in resource-limited areas/countries. 1113…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, results from different studies revealed maternal age above 35, place of residence, level of education, parity, antenatal care (ANC) utilization, place of delivery and mode of delivery, maternal infection and a variety of maternal medical conditions, feto-maternal complications related to pregnancy and labor, inadequate care during pregnancy and immediate childbirth, obstructed/prolonged labor, antepartum hemorrhage, preterm labor, premature rupture of membrane, and intrauterine growth restriction are common obstetric determinants associated with an increased risk of stillbirths, and particularly in resource-limited areas/countries. 1113…”
Section: Introductionmentioning
confidence: 99%
“…Maternal employment was protective of stillbirth 8 . In Ethiopia, predictors of stillbirth were multiple pregnancies and having no prenatal care 20 . In Tanzania and Zambia, the predictor of stillbirth was a previous history of stillbirth 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In a case–control study in southern Ethiopia, the predictors of stillbirth were women with multiple pregnancy [aOR = 2.98, 95%CI: 1.39–6.36], having preterm birth [aOR = 2.83, 95%CI: 1.58– 508], having cesarean mode of delivery [aOR = 3.19, 95%CI: 1.87–5.44], having no ANC visit [aOR = 4.17, 95%CI: 2.38–7.33], and being hypertensive during pregnancy [aOR = 3.43, 95%CI: 1.93–6.06]. [ 22 ]. However, these women were recruited after they had given birth.…”
Section: Discussionmentioning
confidence: 99%